KAJIAN PROGRAM BERITA DI MEDIA TELEVISI - Tri Wahyuti (Program Studi Ilmu Komunikasi Universitas Paramadina, 2015)
In general, television programs can be categorized into two terms, news and non-news programs (entertainment). In the era of the TV industry competition, the television media seek to meet the audience needs by providing news that shows in attractively and informatively. This article will explain the general news programs on television, such as elements in the news program, the stages of work of journalists, and a brief guide to perform a content analysis of media. In the news program elements, this article will explain the important parts that must be considered by newsmakers. In the next section, this article will explain the process of working journalists to make news, from the planning to the delivering stage of news in the media. In the final section, the article will explain about any measuring instrument in the analysis of media content.Key words: news, program, broadcasting, news elements, process of working, journalist, content analysis